Embedding Stand-Alone, 'Local Buzz' and 'Global Pipeline' Firms; a Plea for a Less Traditional Regional Innovation Policy - Evert-Jan Visser; Oedzge Atzema (European Regional Science Association (ERSA), 2006)
This paper deals with the policy implications of a research project based on a non-traditional approach to innovation measurement in a Dutch region. This region is characterized by an 'innovation paradox', as it lodges large numbers of 'creative' people while it also underperforms in traditional innovation measurements. A survey among experts regarding regional innovation yields large numbers of innovative firms in a wide range of industries, which in traditional studies would partly go unnoticed. Further data analysis reveals that innovation in the region has no clear face in terms of firms and sectors. This is due to the embroynic state of clustering in different subsectors, the mostly social and informal nature of network ties between entrepreneurs in the region, the international level at which much innovation-oriented networking takes place, and the lack of connectivity between the latter networks and local informal networks and the embryonic clusters. In terms of their innovation profile, firms in the region are strong in creative, non-technical and combined forms of innovation. So, dynamic capabilities especially show up 'downstream', connecting novelty with clients and markets, and translating this into change management and new practices. Next, we found that firms strategically engage in innovation ventures, in the three ways that were explained before by Bathelt et al. (2004), i.e. seeking and combining international knowledge with one's own (constructing 'global pipelines'), strengthening regional ties, identity, contact and linkages ('local buzz'), and relying on one's own resources for innovation ('stand alone' strategy). One challenge for policy is to exploit these three strategies of firms. Such can be done in three ways. One is to use the abundant social capital in the region, with a view to strengthening the economic relevance of existing local networks by constructing and extending 'global pipelines'. The second is to display leadership and formulate a 'community argument' for innovation (dealing with the following sub questions: why must I innovate, why must I interact in networks and clusters, and why should I do so at different spatial scales?), thus strategically reorienting the available 'local buzz' and enhancing its economic relevance. Together, these two proposals serve the purpose of stimulating knowledge flows 'outside-in' and 'inside-out' (cf. Wolfe & Gertler 2005). The third is to correct for the policy myopia on cluster and network initiatives. The price we pay for the Porterian approach to clustering (cf. Martin & Sunley 2003; Hospers 2005) is that a significant number of firms in the region under review that individually engage in innovation processes, are not part of 'global pipeline' and 'local buzz' processes. Hence, they do not enrich nor benefit from these processes, and may thus relatively easy leave the region. Finally, they may be less effective in innovation, in terms of speed and the market fit of new products and processes. So, both from a regional and firm-level perspective, stand-alone firms merit attention.
Keywords: 330